Study of Cinobufagin as a Promising Anticancer Agent in Uveal Melanoma Through Intrinsic Apoptosis Pathway - Zhang, Leilei; Huang, Xiaolin; Guo, Tao; Wang, Huixue; Fan, Haiyan; Fang, Li (Frontiers in Oncology, 2020)
Uveal melanoma (UM) is the most frequently occurring primary intraocular carcinoma in adults. Cinobufagin, secreted by the Asiatic toad Bufo gargarizans, is a traditional Chinese medicine, widely used for cancer treatment. Here, we explored the potential antitumor function of cinobufagin and investigated its biochemical mechanisms in UM cells. The antitumor potential of cinobufagin was determined via cell viability, cell cycle and apoptosis assays. Colony formation assays confirmed that cinobufagin exerted potent antitumor activity in a dose-dependent manner. We found that cinobufagin could induce cell apoptosis and upregulate the expression of cleaved caspase-3, cleaved PARP, and cleaved caspase-9 in vivo and in vitro. In addition, after treatment with increased concentrations of cinobufagin, the intrinsic mitochondrial apoptosis pathway was also activated, which was demonstrated by increased cell apoptosis with increased expression of Bad and Bax, decreased expression of Bcl-2 and Bcl-xl and reduced mitochondrial membrane potential (MMP) in OCM1 cells. Taken together, the results of this preclinical study suggest that cinobufagin can both inhibit cell survival and induce cell apoptosis in UM cells in a dose-dependent manner, which provides new insights into the biochemical mechanism of cinobufagin and its potential as a future chemotherapeutic agent for UM.